2017
DOI: 10.1038/cdd.2017.184
|View full text |Cite
|
Sign up to set email alerts
|

PAXX and Xlf interplay revealed by impaired CNS development and immunodeficiency of double KO mice

Abstract: The repair of DNA double-stranded breaks (DNAdsb) through non-homologous end joining (NHEJ) is a prerequisite for the proper development of the central nervous system and the adaptive immune system. Yet, mice with Xlf or PAXX loss of function are viable and present with very mild immune phenotypes, although their lymphoid cells are sensitive to ionizing radiation attesting for the role of these factors in NHEJ. In contrast, we show here that mice defective for both Xlf and PAXX are embryonically lethal owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(146 citation statements)
references
References 30 publications
9
135
0
Order By: Relevance
“…TUNEL assay revealed that the levels of apoptosis were almost undetectable in both Paxx −/− and WT brains. We concluded that inactivation of Paxx alone did not affect growth, size, fertility, and development of central nervous system in mice, which is in line with recently published three independent Paxx ‐knockout mouse models .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…TUNEL assay revealed that the levels of apoptosis were almost undetectable in both Paxx −/− and WT brains. We concluded that inactivation of Paxx alone did not affect growth, size, fertility, and development of central nervous system in mice, which is in line with recently published three independent Paxx ‐knockout mouse models .…”
Section: Resultssupporting
confidence: 89%
“…Finally, we analyzed brain sections of WT and Paxx À/À mice and found no difference in neurodevelopment using two independent methods, Nissl staining and TUNEL assay (not shown). While our mouse model was produced and analyzed, three other groups independently reported Paxx-deficient mice [17][18][19]. In contrast to our mouse model, those mice had the entire Paxx locus deleted.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In mice, loss of core C-NHEJ factors leads to apoptosis of post-mitotic neurons and embryonic lethality (Gao et al, 1998;Gu et al, 2000). Moreover, the same synthetic lethal combinations that result in severe lymphocyte developmental blocks (e.g., MRI and XLF) also display similar post-mitotic neuronal apoptosis Abramowski et al, 2018), indicating the critical role of end-ligation and C-NHEJ in the repair of DSBs during neurogenesis.…”
Section: Introductionmentioning
confidence: 99%